The Effectiveness of Electronic Traffic Law Enforcement in Suppressing Traffic Violations: Soerjono Soekanto's Theory Analysis - Nadia Putri Daliuwa; Fenty U. Puluhulawa; Irlan Puluhulawa; Rungarun Boonsayan (al-Battar: Jurnal Pamungkas Hukum, 2026)
Traffic violations remain a persistent problem reflecting the low level of public legal compliance and adversely affecting road safety and traffic order. Previous studies on Electronic Traffic Law Enforcement (ETLE) have generally been descriptive in nature and have focused primarily on the technical aspects of implementation, with limited discussion on the effectiveness of ETLE based on legal effectiveness theory. This study aims to analyze the effectiveness of ETLE implementation in reducing traffic violations within the jurisdiction of the Gorontalo District Court by employing Soerjono Soekanto’s theory of legal effectiveness as the analytical framework. This research uses an empirical legal research method with a mixed-method approach through the analysis of traffic violation statistics from 2023–2025 and interviews with law enforcement officers and members of the public. The findings indicate that ETLE has been effective in the procedural aspect of law enforcement, particularly in improving transparency, objectivity, and administrative efficiency in handling traffic violations. However, substantive effectiveness in reducing the number of traffic violations has not yet been fully achieved due to several factors, including low public legal awareness, limited infrastructure and facilities, and technical constraints within the electronic system. This study contributes to the development of technology-based law enforcement effectiveness studies through an analysis of the factors influencing legal effectiveness according to Soerjono Soekanto, thereby providing a basis for a more comprehensive evaluation of ETLE policies aimed at enhancing sustainable public legal compliance.